2007
DOI: 10.1099/mic.0.2007/007807-0
|View full text |Cite
|
Sign up to set email alerts
|

The β-lactam-resistance modifier (−)-epicatechin gallate alters the architecture of the cell wall of Staphylococcus aureus

Abstract: (")-Epicatechin gallate (ECg), a component of green tea, sensitizes meticillin-resistant Staphylococcus aureus (MRSA) to b-lactam antibiotics, promotes staphylococcal cell aggregation and increases cell-wall thickness. The potentiation of b-lactam activity against MRSA by ECg was not due to decreased bacterial penicillin-binding protein (PBP) 2a expression or ECg binding to peptidoglycan. A 5-10 % reduction in peptidoglycan cross-linking was observed. Reduced cross-linking was insufficient to compromise the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 45 publications
4
103
0
Order By: Relevance
“…Studies with model membranes indicate that flavonoids cause aggregation though [60,61], and in 2007 it was confirmed that the flavonol galangin has this effect on bacterial cells [62]. The flavan-3-ol epicatechin gallate has also been reported to cause bacterial aggregation [19], although it is not yet clear whether this observation was due to genuine aggregation (cells clumping together) or pseudomulticellular bacteria (cells failing to separate following binary fission [54]). An important ramification of this aggregatory effect is that conventional methods are no longer sufficient for demonstrating the bactericidal activity of flavonoids.…”
Section: Identification Of Flavonoid Activity As Bacteriostatic or Bamentioning
confidence: 93%
See 1 more Smart Citation
“…Studies with model membranes indicate that flavonoids cause aggregation though [60,61], and in 2007 it was confirmed that the flavonol galangin has this effect on bacterial cells [62]. The flavan-3-ol epicatechin gallate has also been reported to cause bacterial aggregation [19], although it is not yet clear whether this observation was due to genuine aggregation (cells clumping together) or pseudomulticellular bacteria (cells failing to separate following binary fission [54]). An important ramification of this aggregatory effect is that conventional methods are no longer sufficient for demonstrating the bactericidal activity of flavonoids.…”
Section: Identification Of Flavonoid Activity As Bacteriostatic or Bamentioning
confidence: 93%
“…Most of the reports of flavonoids possessing antibacterial properties can be attributed to these six structures or their isoflavonoid counterparts (flavonoids where ring B is joined at position 3 of ring C instead of position 2). Potential applications for these compounds include modern agents [18] and adjuncts [19] for the treatment of bacterial infections, drugs for treating toxin-mediated disease [20], antivirulence therapies [21] and capture molecules for removing endotoxin from pharmaceutical preparations [22]. In this paper, reports on the diverse range of antibacterial properties exhibited by flavonoids are reviewed.…”
Section: Introductionmentioning
confidence: 98%
“…Many studies was reported that EGCG acts synergistically with various β-lactam antibiotics against MRSA [36]. The polyphenol extract containing epicatechin gallate (ECG), EGC, EGCG, epicatechin and gallocatechin gallate from Korean green tea has antibacterial activity against 13 strains of MRSA clinical isolates and 17 strains of methicillin susceptible S. aureus (MSSA).…”
Section: Combination With Polyphenols and Antibioticsmentioning
confidence: 99%
“…The increasing attraction for the use of phenolics as antibacterial agents maystimulate the use of these extracts as natural food preservatives, potential antibiotic replacements, and as a potential natural source of antimicrobial drugs which will provide novel or lead compounds that may be employed in controlling some infections. [28][29][30][31] CONCLUSION UPLC based metabolite analysis was employed to evaluate the chemical constituents of Eighteen metabolites were identified were synapoylhexose-formic acid, kaempferol 3-O-feruloylhexosyl rhamnoside, 6-Carabinosyl-8-C-glucosyl-apigenin and isorhamnetin-3-O-glycoside-7-O-glycoside reported for the first time from this plant. Its methanol extract showed antibacterial activity was studied in vitro.…”
Section: Anti-bacterial Activity Of Memecylon Talbotianummentioning
confidence: 99%